A 10 year retrospective evaluation of boey score in patients with perforated peptic ulcer in Hospital Universiti Sains Malaysia (January 2004-December 2014) - Rajan Naidu, Ravindera Reddy (2015)
Topic : A 10 years retrospective evaluation of Boey Score in patients with perforated peptic ulcer in HUSM from January 2004 until December 2014. Introduction: For decades, PPU was treated without any risk stratifications though it carries high risk of mortality. Risk stratification is appropriate and imperative to study independent risk factors belonging to patients with particular disease and predict morbidity or mortality. Objective: The objective of this study was to evaluate the Boey Scores in determining mortality outcome of patients presented with PPU. Patients and Methods: The study population consisted of patients who underwent surgery for PPU during the period of January 2004 until December 2014. The number of patients involved in the study were 82. The medical records were traced from the hospital records department after it was permitted by the Director of the hospital.. The relevant socio-demographic, clinical, operative notes and survival status were entered into proforma form. All the data recorded were transferred into SPSS software version 21 and analyzed. Pearson chi-square was used as a statistical test. Significant differences were taken into account if the probability or p value is equal or less than 0.05 Results : The mean age of the PPU patients in this study was 68.5. Malays were the predominant race treated for perforated peptic ulcer. Male patients were higher compared to female with a ratio of 2:1. All the risk factors in Boey scores appeared to be statistically significant in predicting mortality except for the delayed treatment with the range of more or less than 24 hours. Apart from these variables, statistics showes age proven to be a significant risk factor in predicting mortality with the p value of 0.02. Statistically, Boey scores were highly significant in predicting mortality with the p value of < 0.001. This study recorded patients with risk score of zero, one, two, and three has mortality of 0%, 24%, 44% and 32% respectively. Conclusion: Boey scores would be a good scoring system to be used for risk stratification in patients with PPU. Apart from its simplicity, this score statistically proved to be significant in predicting mortality. Age appears to be another statistically proven independent risk factor in this study. However, further studies are needed to study actual outcome in detail.